Specification for harmonized system of quality assessment for electronic components. Blank detail specification. Semiconductor devices. Discrete devices. Field-effect transistors. Blank detail specification for single-gate field-effect transistors, up to 5 W and 1 GHz. (15th December 1988) - British Standards Institution,
No abstract available